Decentralized Frequency Regulation by Using Novel PID Sliding Mode Structure in Multi-Area Power Systems With Hydropower Turbines - Dao Trong Tran; Anh-Tuan Tran; van van Huynh; Ton Duc do (IEEE Access)
This paper introduces a novel sliding mode control (SMC) design utilizing a Proportional-Integral-Derivative (PID) Sliding Surface (SS) for frequency regulation in multi-area electrical power systems (EPSs) with hydropower turbines, accounting for random load conditions, parameter variations, and matched uncertainties. The global system stability of this new approach is mathematically analyzed using Lyapunov theory alongside a novel Linear Matrix Inequality (LMI) technique. A robust strategy is employed through the reaching law method to ensure that frequency deviations converge to zero, even under varying load demands. Despite the presence of parameter variations and random load conditions, the control objectives remain achievable, highlighting the robustness of the proposed method. Moreover, this strategy results in lower overshoot, quicker response times, and reduced chattering effects compared to current traditional SMCs including Proportional-Integral (PI), double PI (DPI), and Proportional-Derivative (PD) sliding surfaces, demonstrating its advantages. Finally, the effectiveness of the suggested scheme is further verified based on three-area EPSs with matched uncertainties, indicating that the proposed scheme achieves stable and robust performance, further confirming its superiority through simulation results.